Efficacy of xenogeneic collagen matrix in the treatment of gingival recessions: a controlled clinical trial - Karyna de Melo Menezes; Samuel Batista Borges; Isadora Medeiros; Gabriela Ellen da Silva Gomes; Angelo Giuseppe Roncalli; Bruno César de Vasconcelos Gurgel (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to evaluate the efficacy of a xenogeneic collagen matrix (XCM) in treating gingival recessions (GR) in a thin gingival phenotype. This double-blind, planned, controlled, split-mouth clinical trial included 30 patients with bilateral recessions, randomly assigned to a test group (extended flap + XCM) and a control group (extended flap + connective tissue graft; CTG). Root coverage at 18 months was 1.75 ± 0.8 mm (72.9%) and 2.4 ± 0.51 mm (88.9%) in the test and the control groups, respectively. The upper limit of the confidence interval was not greater than the non-inferiority margin of 0.69 mm. The increase in gingival thickness was greater for autogenous graft (p = 0.003). Both treatments improved quality of life at 18 months. The keratinized tissue width (KTW) increased significantly in the grafted teeth, in both the test (p < 0.001) and the control groups (p < 0.001). Total root coverage was similar in both groups, reaching 70% and 66.7% in the control and test groups, respectively, with no significant differences observed for partial or complete root coverage (CRC). An association was observed in the quality of the gingival phenotype at 18 months according to the treatment group, i.e., a higher percentage of cases with a thicker phenotype was observed in the control group (86.7%), compared with the test group (53.3%) (p = 0.005). XCM was effective in treating GR, but CTG had better results because of significantly increased gingival thickness and phenotypic conversion.